Environmental degradation in Jacobean drama - Boehrer, Bruce Thomas (Cambridge University Press, 2013)
"In Environmental Degradation in Jacobean Drama, Bruce Boehrer provides the first general history of the Shakespearean stage to focus primarily on ecological issues. Early modern English drama was conditioned by the environmental events of the cities and landscapes within which it developed. Boehrer introduces Jacobean London as the first modern European metropolis in an England beset by problems of overpopulation; depletion of resources and species; land, water and air pollution; disease and other health-related issues; and associated changes in social behavior and cultural output. In six chapters he discusses the work of the most productive and influential playwrights of the day: Shakespeare, Jonson, Middleton, Fletcher, Dekker and Heywood, exploring the strategies by which they made sense of radical ecological change in their drama. In the process, Boehrer sketches out these playwrights' differing responses to environmental issues and traces their legacy for later literary formulations of green consciousness"--